THE ROLE OF DOPPLER REGIMES IN THE DETECTION OF VOLUME OVARIAN FORMATIONS - Ryzhyk, V. M.; Stasiv, I. D. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2022)
In order to increase the diagnostic value of ultrasound diagnostics, qualitative and quantitative Doppler indicators in the detection of bulky ovarian tumors were determined. A comprehensive examination of 149 patients with additional ovarian tumors, which consisted of three groups of patients. The control group included 30 women who did not have large ovarian tumors. Detailed qualitative assessment of blood flow loci was determined using energy Doppler, and quantitative – pulse. The main parameters that were evaluated were maximum blood flow velocity (Vmax), resistance index (IR), pulsation index (PI).Studies have shown that color Doppler showed neovascularity in 46 (95.8%) malignant tumors in contrast to only 35 (68.6%) benign tumors. Malignant tumors are characterized by a change in vascular velocity with an increase in peak systolic velocity and a decrease in the resistance index. Vmax and PI values increase slightly in tumor-like and benign tumors, but in malignant tumors they increase almost twice as much as in the control group (p <0.05), and RI on the contrary - halves in malignant pathology (p <0.05). In 33 (68.8%) cases of ovarian malignancies, the RI was <0.5 and none of the benign tumors had an RI <0.4. Most benign tumors (82.4%) had an RI> 0.6 (p <0.0001).The results of research show that Doppler imaging is an indispensable component of ultrasound in the differential diagnosis of bulky ovarian tumors, as neoangiogenesis has its own characteristics that can be effectively detected using Doppler modes.